UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PEMULAAN ANAK USIA 4-5 TAHUN MENGGUNAKAN MEDIA BUKU FLANEL DI RA AL-HIDAYAH CLARAK LECES PROBOLINGGO - RIRIN ANDRIYANA; Warih Windasari, Indriana (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
This research aims to improve the beginning reading skills of children in group A aged 4-5 years at RA AL-HIDAYAH Clarak-Leces-Probolinggo using flannel book media. The background of this research is the low initial reading ability of children. This research uses the Classroom Action Research (PTK) method which is carried out in two cycles. The model used is the Kemmis and Mc Taggart spiral model which consists of 4 components, namely: planning, implementing actions, observing and reflecting. The indicators studied are that the child understands the picture shown, the child recognizes letters according to the picture shown, the child can arrange a series of letters according to the picture shown, the child knows the letters in the words he sees and the child knows the series of letters that form syllables. The research results show that flannel book media can improve beginning reading skills. At the pre-action stage, the average percentage of children's achievement only reached 18.3%. In the implementation of Cycle I, the percentage achieved was 33.25%, and the achievement of beginning reading skills in Cycle II was 81.5%. The increase from pre-action to Cycle I was 14.95% and the increase from Cycle I to Cycle II was 48.25%. In conclusion, flannel book media can improve the beginning reading skills of group A children at RA AL-HIDAYAH Clarak-Leces-Probolinggo. Keywords: beginning reading, flannel book media, aged 4-5 years